Early Сapitals of Bosporus. A Proportional Analysis - Kolosov, Vladimir P. (Actual Problems of Theory and History of Art, 2017)
The paper presents the potentialities of analysis of Ionian capitals by the method of multidimensional statistics. The study involves 83 artifacts originating from Asia Minor, Attica, the Peloponnese, Graecia Magna and Aegean islands. Chronological framework spans the period from Archaic to Hellenistic times. Ionic capitals were analyzed for 16 criteria, for which proportional relations between their parts were used. As a result,information about regional and chronological differences in the capitals’ proportions was obtained, and the degree of proximity between Ionic capitals made in the Bosporan Kingdom and those derived from other regions of the antique oecumene was revealed. This helped us verify today’s opinions on attribution of early Bosporan capitals, and confirm the supposed date of the objects. Generally speaking, Bosporan capitals, though presenting different variants of Ionic order, demonstrate almost similar proportions: two pieces from Pantikapaion follow Attic models, while other three belong to Asia Minor variety. These observations may indirectly point to stylisticunity of the early Ionic architecture in Bosporus.
Keywords: ancient architecture; Ionic capitals; statistical analysis; architecture of Bosporus